1980
DOI: 10.1007/bf00716372
|View full text |Cite
|
Sign up to set email alerts
|

Arbeitsmedizinische untersuchungen �ber ladearbeiten auf einem gro�flughafen

Abstract: Loading and unloading of aircrafts involves lifting, moving, and carrying of heavy cargo in unfavourable body positions and in narrow spaces. This transport work was subjected to an investigation in a big airport. Forty-three male transport workers and foremen were studied during 46 total shifts. The type of activity was recorded by using the standardized procedure, the so-called "Arbeitswissenschaftliches Erhebungsverfahren zur Tätigkeitsanalyse" (AET). For time and motion analysis, body positions were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…26–28 However, these studies relied on self-reported data about musculoskeletal disorders in small samples and did not include a reference group, and the estimation of exposure was only based on seniority in the occupation and hours per week loading and unloading aircraft. 26 27 …”
Section: Introductionmentioning
confidence: 99%
“…26–28 However, these studies relied on self-reported data about musculoskeletal disorders in small samples and did not include a reference group, and the estimation of exposure was only based on seniority in the occupation and hours per week loading and unloading aircraft. 26 27 …”
Section: Introductionmentioning
confidence: 99%